P837 Incidence, evolution of disease phenotype, time to biological therapy and medium-, long-term surgery rates in IBD-U patients in Western Hungary – a population-based study between 1977–2020, data from the Veszprem county cohort. (30th January 2023) - Gonczi, L; Lakatos, L; Golovics, P A; Pandur, T; David, G; Erdelyi, Z; Szita, I; Lakatos, P L
Abstract: Background: The number of epidemiological population-based studies on unclassified inflammatory bowel disease (IBD-U) patients are very limited. The present study is a continuation of the Veszprem IBD population based cohort with a follow-up of the incidence and disease course of IBD-U since 1977. Our aim was to evaluate incidence, prevalence, disease course, time to biological therapy and surgery rates in a prospective population-based database of incident IBD-U patients diagnosed between 1977 and 2018, with follow-up until 2020. Methods: Both in-hospital and outpatient records were collected. The source of age- and gender-specific demographic data was derived from the Hungarian Central Statistical Office. Medical therapy, time to first biological therapy, disease progression, and colectomy was registered. Results: Data of 119 incident IBD-U patients were analyzed (male/female: 55/64; median age at diagnosis: 34 years(y) (IQR: 24-47)). Adjusted mean incidence rate was 0.76 (CI95%: 0.63-0.9) /10 5 person-years in the total study period, and 0.96 (CI95%: 0.79-1.16) /10 5 person-years between 1990-2018. Disease extent at diagnosis was proctitis in 7.6%, one-sided colitis (left-sided colitis, or isolated right-sided colitis) in 36.1%, and extensive (pancolitis) in 56.3%. The probability of progression in colonic disease extent was 6.7% (SE:2.3) at 3 years, 10.3% (SE:2.8) at 5 years and 15.3% (SE:3.4) at 10 years. Figure 1. The probability of developing terminal ileitis, thus disease classification change – Crohn's disease was 2.6% (SE:1.5) at 5 years and 3.5% (SE:1.7) at 10 years . Figure 2 . Perianal disease developed in 5% (n=6) of all patients during the total follow-up. The probability of receiving biological therapy in patients diagnosed after the year 2000 (n=62), was 15.5% (SE:4.8) at 5 years, and 19.4% (SE:5.3) at 10 years. Figure 3. The overall resective surgery rate was 16.8% at the end of follow-up. Segment resection was performed in 5.0% of the patients, and 11.8% underwent subtotal- or total colectomy. The cumulative probability of resective surgery was 7.6% (SE:2.4) at 1 year, 9.3% (SE:2.7) at 5 years, 13.5% (SE:3.3) at 10 years, and 18.5% (SE:3.9) at 20 years. Figure 4. Conclusion: Initial disease phenotype was severe in most cases of IBD-U and colonic progression is substantial over time. Disease classification change to Crohn's disease with development of terminal ileitis or perianal disease was low. High rates of biological therapy and surgery are suggestive of a severe disease course of IBD-U.